Comparison of Pharmacokinetics and Tissue Distribution Kinetics of Roxithromycin and Expression of CYP 3A1 between Pregnant Mice and Foetuses. Issue 2 (26th October 2016) - Qin, Yi; Xu, Weizhe; Mo, Lanjian; Li, Xiaorong; Ge, Beikang; Xiong, Jie; Gao, Lifang; Xu, Pinxiang; Xue, Ming
Abstract: The roxithromycin, macrolide antibiotics, is recommended for treating mycoplasma infection and has the potential to be administered to pregnant women who are susceptible to the infection. This study compared the pharmacokinetic properties and tissue distribution of roxithromycin among pregnant mice and their foetuses. We also determined the level of CYP3A1, a major enzyme for roxithromycin metabolism, in liver microsomes and investigated the placental transport properties of roxithromycin. Biosamples were collected from female mice at gestational day 17 after a single intragastric administration of roxithromycin. A sensitive and specific liquid chromatography–tandem mass spectroscopy method was developed to detect the drug concentration and to obtain kinetic data. The level of CYP3A1 was significantly lower in foetal liver compared with that in maternal liver according to Western blot data, suggesting a decreased metabolism and prolonged half‐life of roxithromycin in the foetus. The tissue distributions of roxithromycin were similar between mother and foetus, indicating that the placental barrier did not block the transport of roxithromycin from mother to foetus. The current findings are consistent with the clinical efficacy of roxithromycin in both pregnant mothers and foetuses. Based on this study, it is feasible and reasonable to predict the transport properties of other lipophilic drugs during pregnancy.